Breaking the Silence: Stigma, Community Norms, and Social Welfare Responses to Child Sexual Abuse in Zanzibar - Faki, Bakari Khatib; Ali, Juma Salum (Jurnal Sosiologi Agama Indonesia (JSAI), 2026)
Child sexual abuse (CSA) remains a critical social welfare concern in Zanzibar, where disclosure and help seeking are shaped by community norms, stigma, and institutional trust. This study synthesizes secondary sources through qualitative thematic document analysis of peer reviewed literature and policy or organizational reports (2020 to 2025) identified via a structured search and screened for relevance to sociocultural and institutional determinants of reporting and response. The analysis highlights five recurring patterns: (1) disclosure is constrained by collectivist norms that prioritize family reputation and social harmony; (2) victim blaming and gendered expectations intensify stigma and silence; (3) cultural authority and household hierarchies discourage reporting when perpetrators hold status; (4) institutional barriers, including staffing shortages, fragmented referrals, and procedural delays, reduce confidence in formal pathways; and (5) community engagement and integrated service initiatives, including One Stop Centers, show promise but remain unevenly implemented. Using ecological systems thinking and labeling processes, the study argues that silence is reproduced through interactions across community norms, family decision making, and service systems. The paper concludes by recommending culturally grounded, multi-level interventions that strengthen trusted reporting pathways while reducing stigma through community leadership engagement.